Homosexuality and religion in Jeanette Winterson‘s Oranges are not the only fruit and in Nedjma‘s Almond - Ťoukálková, Pavlína (Univerzita Pardubice, 2009)
The expectation is that this paper will initially establish a framework for considering two novels in which the tension/interchange between homosexuality and religion plays a vital role - Jeanette Winterson´s Oranges are not the only fruit and Nedmja´s Almond: The sexual awakening of a Muslim woman (translated by C. Jane Hunter). Secondly - and more to the academic point - it will use this framework to examine how Winterson and Nedmja handle Christian and Muslim contexts, respectively, and the value judgements/implications of homosexuality within those belief systems. The student will be expected to demonstrate a thorough knowledge of the primary texts, as well as to use sufficient secondary sources to explain their contexts.
Keywords: Homosexuality; Religion; the Bible; the Koran; Oranges Are Not The Only Fruit; The Almond; Homosexualita; Náboženství; Bible; Korán; Na světě nejsou jen pometanče; The Almond